Yardstick competition for multi-product hospitals: An analysis of the proposed Dutch yardstick mechanism - Per J. Agrell; Peter Bogetoft; Rein Halbersma; Misja C. Mikkers (Copenhagen Business School (CBS), Department of Economics, 2007)
Health care provision is undergoing major reforms in Europe as a reaction to rapidly increasing expenditure and lowered political acceptance to commit public finance to cover the deficits. The Dutch government will decide in 2007 if the current budget system will be replaced by a more competitive mechanism, based on the yardstick regulation principle by Shleifer (1985). One of the proposed systems for the reform can be compared to a revenue-cap implementation of a multi-product cost-yardstick mechanism. The redistribution of the sector's relevant cost is made in proportion to the individual hospitals share of total weighted output. No regulation is made of the multi-lateral contractual relations between users, insurers and hospitals. The scaling weights are updated periodically for new services and as a function of observed excess demand (waiting lists). The mechanism is shown to provide cost-reducing (effort-inducing) incentives for profit-maximizing rational agents in a single-period bargaining game. The game also shows that the regulation acts as a countervailing power for the insurers to reinforce bargaining power. The local distortion of the output profile induced by the regulation is a function of demand elasticity and cost function convexity. In case the revenue target is not binding, no welfare loss is incurred. The regime also provides incentives for cost-reducing investments in the short and the long run. These incentives manifest themselves in local reallocations of output to more efficient producers. The analysis shows that care should be taken in the updating of the weights as to provide incentives for service innovation, as well as to guarantee convergence of the price system. Although this requires econometric analyses, the alternative with a cost-based yardstick is considered superior to a revenue-based ditto for this application.
hdl:10398/7661
Keywords: G10; 330